WANPRESTASI DALAM POLIS ASURANSI ANTARA PT. MITRA MAKMUR SEJATI UTAMA LOGISTIK DAN PT. ASURANSI HIMALAYA PELINDUNG (Studi Kasus Putusan MA RI Nomor 519/Pdt.G/2018/Pn. Jkt Tmr) - Indah Apriliya (2021)
The agreement is a crucial thing in the engagement. The agreement can run well if the agreement is also based on good faith, but if there are parties who do not carry out good faith including not carrying out their obligations, it can be said as an act of default. In the decision of the Supreme Court of the Republic of Indonesia Number 519/Pdt.G/2018/PN. Jkt Tmr agreement between PT. Mitra Makmur Sejati Utama Logistics with PT. Himalayan Insurance Protector, where the agreement is contained in a policy with Number: 10280311150800025-000059 which became effective on June 2, 2016 with a sum insured of Rp. 2,580,971,000, together with all its addendums. PT. Himalayan Insurance Protector has committed acts of default (breach of promise) where usually the insurance company is the beneficiary party with exoneration clauses that are very in favor of him, but PT. Himalayan Insurance Protector is actually doing the act of default. That the insurance referred to is Insurance for Car Truck Vehicles with police number B 9755 UYU and trucks with police number B 9828 UYU. The purpose of this insurance is to ease the burden of risk faced by the insured by obtaining compensation from the insurer in such a way, In this agreement the plaintiff experiences a robbery on the vehicle that has been insured in this agreement but in this case the defendant commits a default because it does not carry out its obligations as the insurer, it is stated in Article 289 of the Commercial Code that "an insurance can be provided for the full price of the goods insured", then in that case the obligation of the insurer can compensate for the losses suffered by the insured party. The decision contains elements of default (costs, losses, interest) that are not proven, as is the case with Article 1243 of the Civil Code where the seller in this case is clearly negligent and has no good faith (violating the provisions of Article 1338 paragraph 3 of the Civil Code). Civil Law Types of research is used by the author, namely using a normative juridical legal research method. Normative juridical law research is research that uses library sources or secondary materials collected for research and analysis.